Digital twin-driven sustainable energy life cycles: Technical review and Guidelines - Malek Kamal Hussien Rabaia; Concetta Semeraro; Bassel Soudan; Tareq Samir Zaki Salameh; Mohammad Ali Abdelkareem; Abdul Ghani Olabi (Energy Nexus, 2025)
The increasing complexity and inefficiency of traditional energy systems make it difficult to meet the growing global demands for sustainability, resilience, and resource optimization. In response, Digital Twin (DT)-driven sustainable energy life cycles have emerged as a promising solution to address these interconnected challenges. The approaches of sustainability and its development are the most efficient long-term solution for a world where energy, water, food, and security are highly connected yet extremely challenging to provide. Throughout the years, the energy sectors have proved to be the holistic key to ultimately succeed in providing water, food, and security. The massive yet various adoptions and spread of global digitalization, industry 4.0 technologies, and industry 5.0 methodologies have developed Digital Twins (DTs) as an effective and innovative proposal for a sustainable energy life cycle. This work starts with a review-structured introduction, where it critically and comprehensively introduces, discusses, and explains the major concepts of Sustainable Energy and DT technologies, to effectively specify the related research gaps. The paper then takes the reader through the circular journey of energy as an observable entity in a sustainable structure that utilizes DT technology. It is the first paper to provide detailed design guidelines, recommendations, inspirational ideas, and desired DT services. It structures the internal discussions and comparisons within the DT’s literature in the scope of the energy’s renewable generation, sustainable storage, and advanced consumption. Additionally, multiple complex and innovative energy circulation technologies were introduced as strong factors towards sustainable energy life cycles and sectors. Various challenges were addressed regarding the implementation of DTs in the context of sustainable energy. Finally, this work provides a comprehensively detailed guide and an effective starting point for future projects and papers on the utilization of DTs towards sustainable energy life cycles.